Compaction Characteristics and Physical Properties of Compacted Sandy Soil in Indonesia Controlled by the Degree of Saturation - PARAMITHA GUSTI - NIM: 25016015 , TIFANI
In the conventional compaction process, the relationship between the maximum dry unit weight (γd)max and the optimum water content (wopt) is generally used as a reference in compaction control. However, along with the need for higher compaction quality to support the desired structure, higher compaction energy is also needed to achieve these goals. The use of the relationship between the maximum dry unit weight (γd)max to the optimum water content (wopt) has constraints on the use of energy that must be given to the soil and is very sensitive to the type of soil in the field. Based on this, it is proposed to control the degree of saturation (Sr) to be equal to the optimum degree of saturation (Sr)opt of sandy soils in Indonesia in order to obtain the maximum dry density value. The use of the relationship between the maximum dry content weight and the optimum degree of saturation is considered to provide a more independent relationship to the value of the energy used and the type of soil available. The optimum degree of saturation value obtained in sandy soils in Indonesia is in a narrow range when compared to using the relationship between maximum dry unit weight (γd)max and optimum water content (wopt). Based on the testing of the strength of the compacted sandy soil samples through Triaxial Unconsolidated Undrained (UU) tests, a trend of increasing on secant modulus (E50) value when the degree of saturation is decreasing are found. By using the relationship between dry unit weight versus degree of saturation on various levels of compaction energy and different types of soil in Indonesia, it is expected to provide an alternative of controlling process during compaction that is easier than controlling water content.